Pathways to about mental disorders in teaching institutions: An action in mental health with the child-youth public (Research, Society and Development, 2020)
To report health education for adolescents from a public school in a municipality in the interior of the Brazilian Amazon. This is a qualitative, exploratory and descriptive experience report, of a critical-reflexive nature, about a mental health intervention that was based on the problematization method, with the application of the 05 stages of the Maguerez Arch. 50 students from the 6th year of elementary school and 24 students from the 1st year of high school participated in the action, totaling 74 participants, with a total of 37 female and 13 male, between the age group of 13 to 17 years. In this sense, lectures and the creation of therapeutic groups were promoted, in order to provide full attention to the individual needs of each student. There was a deficit in the psychosocial care network, due to the lack of a specific psychological assistance center for young people in the region. Therefore, it was possible to detect possible psychological suffering and assist with pedagogical coordination.